APLIKASI MODEL QUANTUM LEARNING DISERTAI MEDIA FLASH UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATERI PEDOSFER PADA SISWA KELAS XA SEMESTER GENAP SMA NEGERI 5 MAGELANG TAHUN PELAJARAN 2013/2014 - Dini Dwi Yunianti; Peduk Rintayati; Sarwono Sarwono (GeoEco, 2015)
The aims of this research are: (1) enhancing learning motivation through the application of the model material pedosfer Quantum Learning with Flash Media in class XA SMA Negeri 5 Magelang Academic Year 2013/2014, and (2) improving learning outcomes through the application of the model material pedosfer Quantum Learning with Flash Media on XA grade students of SMA Negeri 5 Magelang Academic Year 2013/2014.This research including is Classroom Action Recearch (CAR). The subject of the research is the tenth grade students (XA) of  SMA Negeri 5 Magelang, which has 30 students consisting of: 24 boys and 6 gym girl students class. Its data collecting techniques were gathered through: (1) questionnaire student learning motivation, (2) test student learning outcomes, and (3) documentation. The data analysis technique used is qualitative and quantitative technique. The qualitative data analysis techniques use comparative descriptive analysis where as the quantitative data analysis techniques use comparative analysis.The results: after applying the Quantum Learning Model with Flash Media, it proves that the implementation the Quantum Learning Model with Flash Media can increase the students’ motivation and learning outcomes of XA students of SMA Negeri 5 Magelang. This can be reflected in the motivation and completeness of students’ learning outcomes. It has  increased from the initial condition, the cycle I to the second one. On the initial condition of the students’ learning motivation, there are 5 students or 16,67% who get high motivation in their learning with the class average score 2.29 and 8 students or 16.67% who have got their mastery in their learning with the class average value 65. On the first cycle of the student’s learningmotivation, there are 16 students or 53.33% who get high motivation in their learning with the class average score 2.46 and18 students or 60.00% who have got their mastery in their learning with the class average value of 71,5. In the second cycle there are 21 students or 70.00% who get high motivation in their learning with the class average score  2.63 and  26students or 86,67% who have got their mastery in their learning with the class average value 76.Keywords: Quantum Learning Model Application Accompanied Flash Media, Learning Motivation and Learning Outcomes, Pedosfer.